Historical and Legal Aspects of Participation of the Prosecutor in Civil Proceedings in the Russian Federation - I. I. Golovko; E. A. Goryacheva (Сибирское юридическое обозрение, 2018)
The article is devoted to the study of the development of the legal framework of participation of the Prosecutor in civil cases by the courts since the establishment of the posts of prosecutors in 1722 also Dedicated two new historical conditions, when the prosecution was re-established and empowered to participate in the consideration of cases in courts. Analyzed the reasons for the creation of the prosecution, the powers of prosecutors, the relationship of prosecutors and courts.